Investigating pozzolanic reactivity of micro and nano palm oil fuel ash as cement replacement in mortar - Liew, Yu Xuan (2024)
Palm oil fuel ash (POFA) possesses a pozzolanic activity and is currently underutilized. Thus, POFA may have a potential use as a construction material, and this research focuses on exploring the aforementioned potential. The nano scale palm oil fuel ash (POFA) has a superior particle characteristic and pozzolanic reactivity as cement replacement which may improve concrete or mortar properties. Through the literature review, the nano POFA processing method was limited to the use of high energy ball milling machine and only nano POFA with particle size range between 20 nm to 150 nm were reported. Thus, the various range of nano POFA sizes was made using a Los Angeles (LA) abrasion machine. This work aims to investigate the micro and nano POFA’s particle characteristics, pozzolanic reactivity as well as its impact on the mortar properties. All POFAs were investigated for their particle characteristics in terms of physical properties, chemical composition, mineralogy, morphology, and loss on ignition. Several pozzolanic reactivity assessments such as the Frattini test, Chapelle test, strength activity index (SAI), and thermogravimetric analysis (TGA) were carried out on the micro and all nano POFAs. High-dosage micro (10 to 30%) and low-dosage nano POFA (1 to 3%) were used to replace cement in the high-strength mortar. Those mortars were tested for flowability and hardened properties at the curing ages of 7 to 90 days. The relationship between the factors (micro and all types of nano POFA substation rate) and responses (hardened properties) were expressed in the form of mathematical models using response surface methodology (RSM). The results showed that nano POFAs had a small particle size range (103 to 529 nm), contained a higher amount of silica, aluminium and iron oxide content than that of unprocessed POFA. The nano POFA particle has a smoother surface, is more circular and has a lower crystallinity than the micro POFA. Moreover, all pozzolanic reactivity assessments revealed that nano POFAs showed better pozzolanic reactivity than that of micro POFA. The mortar made of 110k nano POFA had the highest strength (SAI) which is up to 25.5% better than micro POFA mortar. In the TGA and modified Chapelle test, 80k nano POFA was found to consume more calcium hydroxide which indicates its higher pozzolanic reactivity. In terms of mortar’s hardened properties, the optimum mortar mix design contained 10% micro and 3% nano POFA with greater hardened strengths at an increment rate of 1.12 to 7.85% at all curing ages. Increasing the replacement rate of micro POFA up to 30% led to the reduction of mortar’s strength and workability. Increasing the dosage of nano POFA up to 3% helped to improve the strength of mortar that contained 30% micro POFA. Introducing the different particle size ranges of nano POFA in the micro POFA-based mortar led to insignificant changes in its strength as compared to increasing the replacement rate of micro (from 10 to 30%) and nano POFA (from 1 to 3%). The optimization process in RSM showed the solution that contained 10% micro POFA, 3% nano POFA, and the 110k grinding cycle of nano POFA as cement replacement had the highest desirability rate. In conclusion, this research found that the mix design containing 10% micro and 3% nano POFA ground in 110k cycle showed a same level strength contribution to plain cement, leading to the more carbon-free mortar or concrete. Nano POFA with particle size up to 100 nm and lower crystallinity size can be produced from the low grinding speed milling machine and potential for mass production. In addition, the impact of using the nano POFA with particle size ranging from 600 nm to 100 nm as cement replacement in micro POFA-based mortar was tested in this research.